MODES OF PERSUASION IN PRESIDENT JOKO WIDODO’S SPEECH IN 2018 ASEAN WORLD ECONOMIC FORUM: AN ANALYSIS OF POLITICAL DISCOURSE - Juniartha, I Wayan; Pratiwi, Desak Putu Eka (LPPM Universitas Dhyana Pura, 2020)
ABSTRACTPolitical discourse means the text and talk that related with political issues or activities. Thepolitical issues always become controversial in society, the way that makes certain issues becomecontroversial is the act of the actor of politics, as well as the statements delivered in the form ofpolitical speech. The existence of political speech is becoming an essential part in noticing theinfluence of particular political figures, placing his significant role in conducting a politicalmovement to the public, citizens, or particular group from various categories. Language strategy inpolitics is different and unique since it is used to gain attention and even change people perspective.Modes of persuasion plays a very important role in political speech which mainly aims at persuadingand convincing people. The modes of persuasion, often referred to as ethical strategies or rhetoricalappeals, are devices in rhetoric that classify the speaker's appeal to the audience. This study aims atidentifying and analyzing modes of persuasion used in President Joko Widodo’s Speech in 2018ASEAN World Economic Forum. The data were collected by using observation method and notetaking technique. Qualitative method was used to analyze the collected data. They were analyzedby using theory about modes of persuasion as proposed by Aristotle (1962) who divided modes ofpersuasion into ethos, pathos and logos. Our preliminary finding shows that modes of persuasionhas crucial role in delivering political speech since it has power to control people’s behavior.Keywords: persuasion, political speech, ethos, pathos, logosABSTRAKWacana politik adalah teks dan pembicaraan yang berkaitan dengan masalah atau kegiatan politik.Isu politik selalu menjadi kontroversi di masyarakat, cara yang membuat isu tertentu menjadikontroversial adalah ulah para aktor politik, serta pernyataan yang disampaikan dalam bentukpidato politik. Keberadaan pidato politik menjadi bagian penting dalam memperhatikan pengaruhtokoh politik tertentu, menempatkan perannya yang signifikan dalam melakukan gerakan politikkepada masyarakat, warga negara, atau kelompok tertentu dari berbagai kategori. Strategi bahasadalam politik berbeda dan unik karena digunakan untuk menarik perhatian bahkan mengubah carapandang orang. Cara persuasi memainkan peran yang sangat penting dalam pidato politik yangterutama bertujuan untuk membujuk dan meyakinkan orang. Cara persuasi, sering disebut sebagaistrategi etis atau retoris, adalah alat retorika yang mengklasifikasikan daya tarik pembicara kepadaaudiens. Penelitian ini bertujuan untuk mengidentifikasi dan menganalisis mode persuasi yangdigunakan dalam Pidato Presiden Joko Widodo di ASEAN World Economic Forum 2018.Pengumpulan data dilakukan dengan metode observasi dan teknik mencatat. Metode kualitatifdigunakan untuk menganalisis data yang dikumpulkan. Mereka dianalisis dengan menggunakanteori tentang mode persuasi seperti yang dikemukakan oleh Aristoteles (1962) yang membagi modepersuasi menjadi ethos, pathos dan logos. Temuan awal kami menunjukkan bahwa mode persuasiLitera Jurnal Bahasa Dan Sastra 2020memiliki peran penting dalam menyampaikan pidato politik karena memiliki kekuatan untukmengontrol perilaku orang.Kata kunci: persuasi, pidato politik, etos, pathos, logo